IDENTIFICATION OF CUSTOMARY RULES IN PRIVATE FOREST MANAGEMENT ON SIHUTINGCUSTOMARY LAND, ARITONANG VILLAGE,MUARA DISTRICT, NORTH TAPANULI REGENCY - Andrian Sianturi; M. Mardhiansyah; Yossi Oktorini (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2021)
Private forest of Aritonang village is on customary land which is the inheritance of the ancestors in the form of gift/wages by Raja Aritonang to Ompu Guru Sukkunon (a descendant of the Ompusunggu clan) and Ompu Guru Solupa (a descendant of the Rajagukguk clan) are managed based on customary rules. The purpose of this research was to identify the customary rules that apply and to find out the benefits of customary rules in the management of private forests in the customary land of the village of Aritonang. This research was conducted in Aritonang village, Muara Distric, North Tapanuli Regency in April - May 2019. This research used purposive sampling technique to selection of informants. Namely the male lineage and the female lineage of Guru Sukkunon and Guru Solupa who live in hamlet 1 of Aritonang village as much as 36 families, Non-descendant communities Ompu Guru Sukkunon and Ompu Guru Solupa (relatives) who are domiciled in hamlet 1 of Aritonang village as many as 6 families and Batu Binumbun village community who border directly with customary land of Sihuting in Aritonang village as much as 1 family. And this research used qualitative descriptive analysis to analyze the data. Customary rules that apply in the management of Aritonang’s Sihuting private forest cover the process of granting and inheriting management rights of the land land, the time span of use and omission of land, types of plants that are allowed to be planted and/or cared for, yields, establish houses, and determination of sanctions for violators of customary law. The benefits of customary rules in the management of Aritonang’s Sihuting customary forests are the maintenance of order and justice in the process of granting and managing the management rights of customary land